Paediatric Pontine Glioma in Southeast Nigeria: A Case Report - Eneh, C. I.; Egwuonwu, A. C. (British Journal of Healthcare and Medical Research, 2023)
A pontine glioma is a diffuse intrinsic brainstem tumour1,2. Histologically it has a high degree of tumour anaplasia with necrosis (high grade III-IV). The prognosis for intrinsic brainstem glioma is extremely poor as the tumour is inoperable, radiotherapy and chemotherapy are not curative and median survival is less than one year.